Estado nutricional de idosos institucionalizados - Damo, Cássia Cassol (2018)
Malnutrition, commonly found in the institutionalized elderly population, is a result of factors that are characteristic of this age group and of institutionalization, including those related to appetite, dietary intake and nutrient absorption. It is associated with a multiplicity of negative results, which can lead to an increase in costs related to health care and a lower quality of life. The objective of this study was to evaluate the nutritional status and associated factors of institucionalized elderly and to verify the association between nutritional status and sociodemographic characteristics, cognitive decline, and non intentional weight loss. Thus, a crosssectional study was conducted on elderly people living in long-term care institutions in the municipalities of Passo Fundo (RS) and Carazinho (RS) in 2017. This is part of the research project “Patterns of aging and longevity: Biological, educational and psychosocial aspects”. A standardized, pre-codified questionnaire was used with sociodemographic variables, the ones related to Anthropometry, Mini Nutritional Assessment, cognitive decline and non-intentional weight loss. The qualitative variables were presented through univariate frequencies and the quantitative variables were described through measures of central tendency and dispersion. In order to verify the association between categorical variables, the Pearson’s correlation coefficient, Chi-Square test and the Fisher Exact test were applied, and in the crude and adjusted analysis the Poisson regression was used with robust variance. The level of significance was 5%. A total of 399 elderly people, 69.9% were female, 54.5% were aged 80 years or older and 88.4% were white skin color. Of this total, 61.7% are from philanthropic institutions. Through the evaluation of nutritional status, 26.6% of the elderly were malnourished, 48.1% were at risk of malnutrition and 25.3% had normal nutritional status. The highest prevalence ratio of nutritional status at risk/malnutrition was with cognitive decline in the elderly, with unintentional weight loss (p<0.001). The early nutritional evaluation of institutionalized elderly allows establishing the appropriate evaluation protocol for each situation and thus prevent health problems. It is suggested to carry out new studies with the same theme in order to improve care for these elderly people. This dissertation is composed by an introduction, bibliographic review, scientific production entitled "Risk of malnutrition and associated factors in institutionalized elderly", final considerations, references, and attachments.